2021
DOI: 10.1149/2162-8777/abdc41
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting Polycrystalline Silicon Layer Obtained by Boron Implantation and Nanosecond Laser Annealing

Abstract: In this work, we report on the material properties of superconducting heavily boron-doped polycrystalline Silicon-On-Insulator (SOI) thin layers fabricated by pulsed laser induced recrystallization under experimental conditions compatible with high volume CMOS integration. This approach combines boron implantation and ultra-violet nanosecond laser annealing (UV-NLA) to reach maximum dopant activation by exceeding boron solid solubility in silicon. For our process conditions, material characterizations revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In these cases, the concentration of active dopants can reach atomic percentages as high as 5–10%, exceeding the crystal solubility limit. Ultradoping involves utilizing high doping concentrations to achieve superconductivity, whereas hyper-doping is linked to augmenting semiconductor bands to increase absorption coefficients and enhance plasmonic effects in the infrared region. A successful completion of laser melting processes requires an in-depth design of experiments, often coupled to precise calculations. To this purpose, having an exhaustive comprehension of crystalline and liquid optical functions is essential.…”
Section: Introductionmentioning
confidence: 99%
“…In these cases, the concentration of active dopants can reach atomic percentages as high as 5–10%, exceeding the crystal solubility limit. Ultradoping involves utilizing high doping concentrations to achieve superconductivity, whereas hyper-doping is linked to augmenting semiconductor bands to increase absorption coefficients and enhance plasmonic effects in the infrared region. A successful completion of laser melting processes requires an in-depth design of experiments, often coupled to precise calculations. To this purpose, having an exhaustive comprehension of crystalline and liquid optical functions is essential.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of group IV elemental and compound semiconductor processing, pulsed-LA applications are ubiquitous. ,, These include the fabrication of poly-Si thin-film transistors, ultrashallow device junctions, , efficient contacts by silicidation, explosive crystallization, strain, defect, , and dopant engineering. Localized heating minimizes the risk of damaging sequentially integrated components of monolithic three-dimensional (3D) devices. In optoelectronics, pulsed-LA is a key process for fabricating poly-Si displays, thin metal-oxides, pure-carbon electrodes for touch screens or solar cells, and hyper-doped semiconductors for near-infrared photodetectors . It also allows strain, composition and morphology engineering of fiber-based photonic devices, and fabrication of heavily doped superconducting silicon for monolithic quantum device integration. , Despite all of these applications, understanding the ultrafast nonequilibrium kinetics of the liquid/solid interface in early stages of the process and correlating it to the postirradiation morphology and properties is challenging. This is because any experimental characterization, no matter how accurate, can only access the final state of the system.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, it was shown that the electrically active carrier concentration in binary Si:P could be significantly increased by nanosecond laser annealing thanks to its ability to dissolve P clusters [5]. In binary Si:B, superconductivity was achieved by electrically activating ultra-high B concentrations [6]. In-situ doping Ge with B resulted in binary alloys [7] with metastable, ultra-high substitutional concentrations.…”
Section: Introductionmentioning
confidence: 99%